Measuring surface texture of in-service asphalt pavement: evaluation of two proposed hand-portable methods. Issue 2 (1st February 2023) - Matlack, Glenn R.; Horn, Andrea; Aldo, Aldo; Walubita, Lubinda F.; Naik, Bhaven; Khoury, Issam
Abstract : Road managers require convenient, inexpensive methods to quickly assess pavement conditions over large areas. New imaging technologies potentially offer a substantial improvement over current methods. In this study, two hand-portable methods based on widely available consumer-grade technology were tested across a range of pavement conditions. To place the proposed methods in a familiar context, data were compared with the mean texture depth (MTD) calculated by the widely used volumetric method. MTD provided the clearest distinction between experimental roughness classes. Spatial pattern analysis (fractal dimension) of digital images discriminated between light, moderate and severe deterioration but failed to make fine distinctions between degrees of moderate wear. Three-dimensional models constructed by stereoscopic infrared scanning distinguished between all but the smoothest texture classes. It appears that both the proposed methods have potential for accurate, quick and convenient assessment of pavement macrotexture at little expense, although some judgement must be used in their application.